Effect of Terminological Analysis on Linguistics - Dalieva Madina Xabibullaevna (Genius Journals, 2023)
The article discusses terminology as a branch of linguistics and the conditions under which words arise and develop. By transferring the correct meanings of phrases, terminology may be seen of as a discipline that aids in bridging gaps and extending one field into another. Additionally, the article provides concise examples to illustrate the key terminology formation techniques.
Keywords: Terminology; Sociolinguistics; Lexicography